AN ASSESSMENT OF THE POST-REHABILITATION (FERTILIZATION) OF COCONUT IN SCFDP FARMS, PHILIPPINES - Severino S. Magat , Ph.D (International Coconut Community, 1999)
Selected sample farms (79) under the Small Coconut Farms Development Project (SCFDP, Philippines) representing five (5) regions and nine (9) provinces were evaluated. The yield trends: (1) initial or benchmark; (2) during rehabilitation period (3-4 years); and (3) post-rehabilitation period (2) years were examined using the nut and copra yield estimation method of the PCA (MAGAT, 1995). On nut yield, the benchmark average annual yield of 35 nuts/tree increased to 91 nuts/tree during the rehabilitation (rehab) period but dropped to 70 nuts/tree during the post-rehabilitation (post-rehab) period or two (2) years without fertilizer application. This 160% increase in nut production (1995) followed by a reduction of 23% at the post-rehab period is indicative of a moderate to strong residual fertilizer effect after the significant rehabilitation of palms by fertilizer application (supplying mainly N, K, Cl and S fertilizer nutrients). On copra yield, the pre-rehabilitation annual copra yield of 0.94 t ha reached 3.01 t/ha during the rehab period, followed by a drop to 2.21 t/ha at post-rehab. The copra yield increase of 220% during the rehab (1995) is mainly due to the increase in nut yield and nut size or copra weight per nut. An average reduction of 27% during the post- rehab period was observed but in some areas the yield of palms dropped close to pre-rehabilitation nut and copra levels, suggesting lower degree of fertilizer residual effects compared to other coconut regions. Implications of findings in relation to the rehabilitation by judicious fertilization of low-yielding, nutritionally-deficient non-senile palms are discussed.